Assessing the Vestibulo-ocular Reflex of Contralesional Sides According to Head Impulse Velocity Utilizing the Video Head Impulse Test in Patients with Vestibular Neuritis - Wonyong Baek; Young Jae Lee; Jeonghyun Oh; Sung Il Cho; Gi-Sung Nam (Journal of International Advanced Otology)
BACKGROUND: There is a lack of comparative studies examining changes in vestibulo-ocular reflex (VOR) gain with head velocity in the video head impulse test (vHIT) of patients with vestibular neuritis (VN). Thus, the purpose of present study was to identify the effect of head impulse velocity on the gain of the VOR during the vHIT in patients with VN.